(untitled) (Fiep Bulletin - online, 2011)
Introduction: The Achilles tendon is commonly affected by traumatic injuries that lead to inflammation and edema. When the immune system is altered, there is a low immune response, which can lead to a slowing of tissue recovery. Thus, the low level laser therapy can be used for presenting beneficial effects in this type of injury. Thus, the goal of this study was to determine whether the low level laser therapy is effective for the treatment of edema in rats immunosuppressed undergoing tendon trauma. Materials and Methods: 23 male rats of Wistar strain were divided randomly into control group, placebo and laser. The animals were immunosuppressed and subjected to a lesion in the right Achilles tendon. For treatment, we used low level laser therapy, 660 nm, 30 mW and dose 2 J/cm2. Results: There was a significant decrease in the diameter of the tendons in the GP, between post-injury and four, 24 and 48 hours after injury and in the GL, the results were significant between post-injury, 24 and 48 hours after injury. Conclusion: The low level laser therapy is effective to reduce edema in immunosuppressed rats underwent tendon trauma.